Substitution of natural feed with artificial feed on the survival rate and growth rate of giant-snakehead Channa micropeltes - Sarmila; Susilawati, Susilawati; Warastuti, Sri (Indonesian Society of Scientific Aquaculture (ISSA), 2021)
The purpose of this study was to determine the best percentage of artificial feed substitution for growth and survival rate of giant-snakehead. This study used a completely randomized design (CRD) with 4 levels of artificial feed substitution dose treatment, namely 25%, 50%, 75%, 100%, and control (without artificial substitution). The feed used in the form of fresh trash fish mixed with artificial feed FF-999 with a protein content of 35%. The results showed that the control treatment (100% trash fish) gave the best survival rate and spesific growth rate of 75% and 2.12%/day, respectively. Meanwhile, the percentage of artificial feed substitution treatment which gave the best survival rate and specific growth rate was found in the substitution percentage treatment of 25% artificial feed with a survival rate of 66.67% and a daily weight growth rate of 1.89%/day. Substitution of 100% artificial feed caused death with a 0% survival rate. Keywords: artificial feed, feed substitution, giant-snakehead, survival rate, growth ABSTRAK Penelitian ini bertujuan menentukan persentase substitusi pakan buatan yang terbaik untuk laju pertumbuhan, dan tingkat kelangsungan hidup ikan toman. Penelitian ini menggunakan rancangan acak lengkap (RAL) dengan perlakuan 4 level dosis substitusi pakan buatan yaitu 25%, 50%, 75% dan 100% serta 1 kontrol (tanpa substitusi pakan buatan). Pakan yang digunakan berupa ikan rucah segar dicampur dengan pakan buatan berupa pellet dengan merk FF-999 berkadar protein 35%. Hasil penelitian menunjukkan bahwa perlakuan kontrol (100% ikan rucah) memberikan tingkat kelangsungan hidup dan laju pertumbuhan berat harian terbaik masing-masing sebesar 75% dan 2.12%/hari. Sementara untuk perlakuan persentase substitusi pakan buatan yang memberikan tingkat kelangsungan hidup dan laju pertumbuhan terbaik terdapat pada perlakuan persentase substitusi sebesar 25% pakan buatan dengan tingkat kelangsungan hidup 66.67% dan laju pertumbuhan berat harian 1.89%/hari. Substitusi 100% pakan buatan menyebabkan kematian dengan tingkat kelangsungan hidup 0%. Kata kunci: ikan toman, kelangsungan hidup, laju pertumbuhan, pakan buatan, substitusi pakan.